2018
DOI: 10.1186/s12977-018-0414-5
|View full text |Cite
|
Sign up to set email alerts
|

New World feline APOBEC3 potently controls inter-genus lentiviral transmission

Abstract: BackgroundThe apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like 3 (APOBEC3; A3) gene family appears only in mammalian genomes. Some A3 proteins can be incorporated into progeny virions and inhibit lentiviral replication. In turn, the lentiviral viral infectivity factor (Vif) counteracts the A3-mediated antiviral effect by degrading A3 proteins. Recent investigations have suggested that lentiviral vif genes evolved to combat mammalian APOBEC3 proteins, and have further proposed that the Vif-A3 int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 57 publications
(100 reference statements)
1
23
1
Order By: Relevance
“…Since previous studies indicate that A3 proteins likely play a role in limiting and controlling PLV infection of domestic cats [53,66], these findings suggest that constitutive, rather than regulated levels of cat A3 can be sufficient to inhibit lentiviral cross-species infection. Lentiviral Vif may evolve to counter A3 restriction, resulting in competent infection and enhanced virulence, so the ultimate outcome of an evolutionary conflict between cat A3 and a non-adapted FIV is dependent upon both host and viral adaptation [16,45,67]. Even in the case of a host-adapted lentivirus, there is likely a dynamic balance between A3-mediated restriction and Vif-mediated protection.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies indicate that A3 proteins likely play a role in limiting and controlling PLV infection of domestic cats [53,66], these findings suggest that constitutive, rather than regulated levels of cat A3 can be sufficient to inhibit lentiviral cross-species infection. Lentiviral Vif may evolve to counter A3 restriction, resulting in competent infection and enhanced virulence, so the ultimate outcome of an evolutionary conflict between cat A3 and a non-adapted FIV is dependent upon both host and viral adaptation [16,45,67]. Even in the case of a host-adapted lentivirus, there is likely a dynamic balance between A3-mediated restriction and Vif-mediated protection.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests the possibility that bobcats intrinsically have species barrier(s) that restrict PLV-B infection. Konno et al showed that puma and bobcat APOBEC3Z3 proteins (the orthologs of human APOBEC3H) can be antiviral [ 56 ]. Intriguingly, puma APOBEC3Z3 protein is degraded by both the PLV-A and PLV-B Vif proteins, while bobcat APOBEC3Z3 protein is degraded by PLV-A Vif but is resistant to PLV-B Vif [ 56 ].…”
Section: Role Of Mammalian Apobec3 Proteins In Cross-species Lentimentioning
confidence: 99%
“…Konno et al showed that puma and bobcat APOBEC3Z3 proteins (the orthologs of human APOBEC3H) can be antiviral [ 56 ]. Intriguingly, puma APOBEC3Z3 protein is degraded by both the PLV-A and PLV-B Vif proteins, while bobcat APOBEC3Z3 protein is degraded by PLV-A Vif but is resistant to PLV-B Vif [ 56 ]. These findings suggest that the cross-species transmission of PLV-B from pumas to bobcats can be hampered by bobcat APOBEC3Z3 protein.…”
Section: Role Of Mammalian Apobec3 Proteins In Cross-species Lentimentioning
confidence: 99%
“…Recent investigations have suggested that lentiviral vif genes evolved to combat mammalian APOBEC3 proteins, and have further proposed that the Vif–A3 interaction may help to determine the co-evolutionary history of cross-species lentiviral transmission in mammals [ 151 ]. In most cases, the interaction of Vif with A3 proteins is species-specific [ 152 ], but some lentiviral Vif proteins are capable of triggering the degradation of A3 proteins of several other mammals in addition to their natural host species [ 153 ].…”
Section: Host Restriction Factorsmentioning
confidence: 99%
“…However, differences are seen, as puma lentiviruses group A (PLV-A) counteract the antiviral action of A3Z3 of both puma and bobcat, whereas PLV-B Vif counteracts only puma A3Z3. The amino acid at position 178 in the puma and bobcat A3Z3 is exposed on the protein surface, and determines the sensitivity to PLV-B Vif-mediated degradation [ 151 ].…”
Section: Host Restriction Factorsmentioning
confidence: 99%